CADASTRAL DELIMITATION OF ADMINISTRATIVE TERRITORY IN ROMANIA, IN ORDER TO ACHIEVE GENERAL URBAN PLANS (PANGEEA, 2025)
Cadastral delimitation of territorial administrative units represents a basic activity in order to identify, measure and establish the limits of the territorial administrative units, containing significant points and border path of the territorial administrative unit, but also the urban area border. The general urban plan is the main strategic document that establishes the priorities of the economic, social and cultural development. The urban activity without a general urban plan is nothing else but chaos. The general urban plan is a project according to the regional planning and urban development for all the urban area of the territorial administrative unit. It involves a series of analyses, regulations and local statutes for the entire administrative territory (both intravilan and extravilan). In the same time, the general urban plan establishes general norms that will be the base of the detailed plans, zonal urban plan and detailed urban plan.
Keywords: Cadastral delimitation; general urban plan; administrative territory